An analysis of the trends of managers in commercial banks in Taif Governorate towards the application knowledge management processes - Salih, Amir Omer Hassnain (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aims to identify the trends of managers in commercial banks towards the application of knowledge management processes in Taif governorate in Saudi Arabia. To achieve the objectives of the study, the researcher developed a questionnaire of (27) paragraphs divided into three dimensions. The study community consisted of all managers in commercial banks in Taif. The resolution analyzed using (SPSS). The study found a set of results, the most prominent of which were: The existence of significant effect at the level of statistical indication (a=0.05)of knowledge management processes diagnosis, generation, storage, transport and application) in commercial banks in Taif. There is a statistical difference of (a=0.05) to arrange the areas of knowledge management processes from the point of view of managers in commercial banks in Taif governorate. The most important findings of the study: The need to urge all managers working in commercial banks in Taif governorate to use their own knowledge to solve the problems and obstacles they are exposed to so that there is creativity and innovation. Create a database of experts and consultants from managers and knowledge- conscious, and their knowledge innovations so that they can benefit from their expertise and opinions in developing knowledge them to commercial banks in Taif.
Keywords: Operations; Knowledge Management; Commercial Banks